Dietary patterns in a nursing team measured by principal component analysis - Barreiro, Patricia Lima Dias; Vasconcelos, Ana Glória Godoi; Rotenberg, Lucia; Griep, Rosane Harter; Aguiar, Odaleia Barbosa de (Revista da Escola de Enfermagem da USP, 2020)
Objective: To characterize the dietary pattern of nursing professionals at a public hospital in Rio de Janeiro, RJ, Brazil. Method: A sectional study with nursing professionals (nurses, technicians and nursing assistants). Two 24-hour food recall records were applied, totaling 459 foods, being reduced to 24 food groups. Food patterns were identified using the Principal Component Analysis technique, followed by orthogonal varimax rotation. A Scree Plot graph indicated three factors to be extracted and loads > +0.30 were adopted to define dietary patterns. Results: A total of 309 professionals participated. The sample consisted of 85.8% of female individuals. The patterns were named “traditional” which included rice (0.747), beans (0.702) and meat (0.713); “healthy”: vegetables (0.444), greens (0.450), fruits (0.459), bananas and oranges (0.379), and “snacks”: sugar (0.661), bread (0.471), cakes and cookies (0.334), non-alcoholic drinks (0.727). Conclusion: The results highlight the “traditional” food pattern of Brazilian food consumption based on the combination of rice, beans and meat. Future studies may investigate the effect of dietary patterns on health outcomes among nursing workers.